The Indirect Cost of Natural Disasters and an Economic Definition of Macroeconomic Resilience - Hallegatte, Stephane (World Bank, Washington, DC, 2015)
The welfare impact of a disaster does not depend only on the physical characteristics of the event or its direct impacts in terms of lost lives and assets. Depending on the ability of the economy to cope, recover, and reconstruct, the reconstruction will be more or less difficult, and the welfare effects smaller or larger. This ability, which can be referred to as the macroeconomic resilience of the economy to natural disasters, is an important parameter to estimate the overall vulnerability of a population. Here, resilience is decomposed into two components: instantaneous resilience, which is the ability to limit the magnitude of the immediate loss of income for a given amount of capital losses, and dynamic resilience, which is the ability to reconstruct and recover quickly. The paper proposes a rule of thumb to estimate macroeconomic resilience, based on the interest rate (a higher interest rate decreases resilience and increases welfare losses), the reconstruction duration (a longer reconstruction duration increases welfare losses), and a “ripple-effect” factor that increases or decreases immediate losses (negative if enough idle resources are available to cope; positive if cross-sector and supply-chain issues impair the production of non-affected capital). An optimal risk management strategy is very likely to include measures to reduce direct impacts (disaster risk reduction actions) and measures to reduce indirect impacts (resilience building actions).